Valuation Of Reload Call Option With Binomial Tree - Yunita Wulan Sari, Yunita Wulan Sari (2016)
Along with the rapid growth of investment and finance, the investors compete with each other to find a way to maximize pro_ts and minimize losses. In option trading, one of the ways used is adding a reload feature on the option. Reload option is option thatgive the right to its holder to exercise the option, then renew it at some time prior to maturity. In this research, we study how to determine the pricing of reload call option with the Black-Scholes stock price model and the binomial tree, then applied to the stock of Telekomonikasi Indonesia (TLKM.JK). From this study, we obtain the valuation of reload call option which is simple and easy in interpretation. In addition we can also conclude that if the time to maturity is longer, the price of reload call option is more expensive and if the exercise price is higher, the price of reload call option is cheaper.